THE IMPACT OF JOB PLACEMENT ON WORK EFFECTIVENESS GOVERNMENT EMPLOYEES AT THE REGIONAL OFFICE MINISTRY OF RELIGIOUS AFFAIRS OF NORTH SUMATRA - Insan, Muhammad Yalzamul; Wulandari, Niken; Pangestu, Bagus (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This research was conducted to find out how the influence of job placement on the work effectiveness of employees at the Regional Office of the Ministry Religion Affairs of North Sumatra. This research used quantitative data processed with SPSS 24.0 used are regression analysis, The number of samples taken as many as 73 respondents calculated by the Slovin formula. The results showed that job placement, partially had a positive and significant effect on the work effectiveness of civil servants in the Regional Office of the Ministry of Religion of North Sumatra.